Exploring Lecanemab: Mechanisms, Efficacy, and Clinical Implications in Alzheimer’s Disease Management - He, Ziming (Transactions on Materials, Biotechnology and Life Sciences, 2025)
Lecanemab, with accelerated approval from the FDA, becomes a notable and promising drug to fight against Alzheimer’s disease (AD). As one monoclonal antibody, it is reported that lecanemab can reduce cognitive decline caused by AD by reducing amyloid-beta in patients. However, some concerns, uncertainties and limitations of Lecanemab in clinical trials have also been brought out. This study analyses the existing methods to cure AD and researches in clinical phases of lecanemab and relevant detailed information. This article aims to provide a relevant view of key aspects of lecanemab’s performance, including its mechanisms, effects, safety, limitations and tips. Thus, this study shows an updated summary for those who want to be exposed to the current situations of applications of Lecanemab. The nature of AD remains complex to us nowadays, so further fundamental research concerning the causes and mechanisms of AD. For those drugs targeting AD, many aspects involving itself and its usage still need to be investigated.